Модель интеллектуальной информационной системы для образования - Kaziakhmedov T. B., Mosiagina T. V. (Pedagogics and psychology: relevant theoretical and practical questions, 2016)
Informatization of education today poses new demands on information systems, chief among them is their intellectualization. Introduction to information systems elements of artificial intelligence on all levels of their development and use – the future of information systems in education. This article discusses a model of such an information system.
Keywords: искусственный интеллект; artificial intelligence; компоненты образовательных информационных систем; модуль реализации предметного содержания; модуль интеллектуализации; модуль правил; модуль обучения; модуль самообучения; components of educational information systems; module of the implementation of subject content module intelligent module rules; module learning; self-learning module